Berbagi Pengetahuan dan Perilaku Inovatif Siswa di Pendidikan Tinggi: Systematic Literature Review Tentang Kekuatan Hubungan, Mediasi, dan Konteks Pembelajaran - Partono Nyanasuryanadi; Kinanti Dyah Ayu Puspita Retno Putri (Educational Journal, 2026)
The development of higher education in the knowledge-based economy era demands strengthening students' innovative behavior as one of the primary learning outcomes. Innovation is influenced not only by individual abilities but also by social processes within the learning environment, one of which is through knowledge sharing practices. This study aims to systematically examine the relationship between knowledge sharing and students' innovative behavior, the underlying mechanisms, the forms of practices implemented, the educational context, and the outcome measures used in previous research. The method used was a Systematic Literature Review (SLR) of 50 relevant peer-reviewed journal articles. The analysis was conducted using a thematic approach and narrative synthesis. The results indicate that knowledge sharing has a positive and significant relationship with students' innovative behavior, with varying strengths. This relationship is generally mediated by psychological factors such as self-regulated learning and innovation self-efficacy, and moderated by contextual conditions such as innovation climate and collaborative culture. Collaborative knowledge sharing practices, both face-to-face and digital, are the most dominant and effective forms in fostering innovation. These findings emphasize the importance of integrating knowledge sharing into learning design as a strategy for developing students' innovative behavior in higher education.